The impact of perioperative red blood cell transfusions in patients undergoing liver resection: a systematic review. Issue 4 (April 2017) - Bennett, Sean; Baker, Laura K.; Martel, Guillaume; Shorr, Risa; Pawlik, Timothy M.; Tinmouth, Alan; McIsaac, Daniel I.; Hébert, Paul C.; Karanicolas, Paul J.; McIntyre, Lauralyn; Turgeon, Alexis F.; Barkun, Jeffrey; et al.
Abstract: Background: Liver resection is associated with a high proportion of red blood cell transfusions. There is a proposed association between perioperative transfusions and increased risk of complications and tumor recurrence. This study reviews the evidence of this association in the literature. Methods: The Medline, EMBASE, and Cochrane databases were searched for clinical trials or observational studies of patients undergoing liver resection that compared patients who did and did not receive a perioperative red blood cell transfusion. Outcomes were mortality, complications, and cancer survival. Results: Twenty-two studies involving 6832 patients were included. All studies were retrospective, with no clinical trials. No studies were scored as low risk of bias. The overall proportion of patients transfused was 38.3%. After multivariate analysis, 1 of 5 studies demonstrated an association between transfusion and increased mortality; 5 of 6 demonstrated an association between transfusion and increased complications; and 10 of 18 demonstrated an association between transfusion and decreased cancer survival. Conclusion: This review supports the evidence linking perioperative blood transfusions to negative outcomes. The most convincing association was with post-operative complications, some association with long-term cancer outcomes, and no convincing association with mortality. These findings support the initiation, and further study, of restrictive transfusion protocols.